KAJIAN PERILAKU HEDONISME AKUN AWKARIN DALAM INSTAGRAM - Syafitri, Dely; Faizah, Hasnah; Auzar, Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstact: In essence, humans are social beings, namely beings who need other people to fulfill the needs of life and survival, for which humans live to communicate in an environment and interact with each other. The lifestyle of hedonism is a pattern of life that seeks pleasure such as spending a lot of time outdoors, playing more and enjoying buying expensive items.Research refers to psycholinguistic theory which means the science that studies language behavior, both visible behavior and invisible behavior. in the form of perception, language production, and language acquisition. Behavior that appears in language is human behavior when speaking and writing or when he produces language, whereas behavior that is not visible is human behavior when understanding what is read or read so that it becomes something that it has or processes something that will be said or written.The behavior of hedonism through Instagram social media in the form of self-expression means that a view of life is assumed that someone will be happy by looking for as much happiness as possible to avoid painful feelings, and that pleasure or pleasure is the purpose of life for those who participate in enlivening Instagram social media which is mostly done especially for teenagers today. Overall, this study shows the behavior of egoistic hedonism from the first appearance that the researchers consider the photo to be a picture of the attitude of hedonism raised by Awkarin. It also reflects a luxurious lifestyle and spree. And not only that the description of the post exposes words that are considered luxurious and sometimes seem impolite, using the word reflects hedonism.Key Words: Behavior of Hedonism, Psycholinguistics, Instagram